Theatre, training, and life in Goethe’s Wilhelm Meister - Werle, Marco Aurelio; Restrepo , Carlos Enrique (Estudios de Filosofía, 2013)
This article presents a study of Goethe’s Wilhelm Meister’s apprenticeship, particularly of The years of learning with respect to the genre that romanticism defined as a “novel of education” (Bildungsroman). It also takes into consideration the initial version of the novel, titled The theatrical calling. The fundamental issue is that of being formed by the theater, which is much more than just an artistic ideal because it involves the identification of theater and life, which determines the work of formation as based on freedom.